2018
DOI: 10.1080/15592294.2018.1465790
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers for head and neck squamous cell carcinoma

Abstract: DNA methylation plays an important role in the etiology and pathogenesis of head and neck squamous cell carcinoma (HNSCC). The current study aimed to identify aberrantly methylated-differentially expressed genes (DEGs) by a comprehensive bioinformatics analysis. In addition, we screened for DEGs affected by DNA methylation modification and further investigated their prognostic values for HNSCC. We included microarray data of DNA methylation (GSE25093 and GSE33202) and gene expression (GSE23036 and GSE58911) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 55 publications
2
52
0
Order By: Relevance
“…The TCGA consortium identified four methylator subtypes associated with colorectal cancer, each associated with differing clinico-pathological characteristics (5). In head and neck squamous cell carcinoma (HNSCC), analysis of TCGA tumour methylation data has revealed both hyper-and hypomethylated gene sets for diagnostic purposes (6).…”
Section: Resultsmentioning
confidence: 99%
“…The TCGA consortium identified four methylator subtypes associated with colorectal cancer, each associated with differing clinico-pathological characteristics (5). In head and neck squamous cell carcinoma (HNSCC), analysis of TCGA tumour methylation data has revealed both hyper-and hypomethylated gene sets for diagnostic purposes (6).…”
Section: Resultsmentioning
confidence: 99%
“…The redundant biomarkers tended to cause over-fitting of the classifier and resulted in poor generalization performance, while fewer biomarkers including incomplete or damaged information often resulted in under-fitting. Although DNAm was an important biological phenomenon in the development of many different types of cancer, there was a lack of greater insight into the physiological mechanisms of disease based solely on DNAm (Vrba et al, 2020;Zhou et al, 2018). Therefore, our multi-omics-based analysis provided a unified view for understanding the interrelationship between different molecular mechanisms and the combined effects on disease processes as well as for screening biomarkers with high sensitivity and specificity (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a number of studies have indicated that increased FAM135B expression can enhance the malignant phenotype of ESCC, reflected by the promotion of cell proliferation, metastasis and invasion. Furthermore, high FAM135B expression may be associated with endogenous phosphoglyceraldehyde dehydrogenase (28,41). This suggests that FAM135B is closely associated with the occurrence and development of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the FAM135B gene is located in human chromosome 8q24.23 (27). A number of studies have demonstrated that the FAM135B gene is associated with the occurrence and development of tumor, and can promote the proliferation, migration and invasion of tumor cells (11,14,28).…”
Section: Introductionmentioning
confidence: 99%